Demographic Factors as a Catalyst for the Retention of Academic Staff: A Case Study of Three Universities in Sub - Saharan Africa - Gurmessa, Z. B.; Ferreira, I. W.; Wissink, H. F. (Journal of Economics and Behavioral Studies, 2018)
The aim of the study was to determine the effect that demographic factors such as age, gender, marital status and education, as well as factors such as years of experience, income, academic rank, country of origin and area of specialisation have on academic staff working in the higher education sector in Sub Saharan Africa . A survey approach was adopted as the main data collection tool and data was collected from three public Universities - University of KwaZulu- Natal (UKZN), Addis Ababa University (AAU) and Haramaya University (HU). The first university is located in South Africa and the last two universities are situated in Ethiopia. The survey was employed as a research design. A self- administered survey questionnaire consisting of both demographic variables (age, tenure, educational level, academic rank, employment status, marital status, average income level, and fields of specialisation) and six item turnover intentions or intentions to stay variables (measured a five -point Likert Scale in which 1= Strongly Disagree; 2= Disagree; 3= Neither Agree Nor Disagree; 4= Agree and 5= Strongly Disagree) were completed by 596 respondents selected by means of the stratified sampling method. The data was analysed using the Statistical Package of the Social Sciences(SPSS) software packages version 24. Both descriptive (frequencies, mean and standard deviation) and inferential (one-way-ANOVA) statistics were applied to examine the effect of the various demographic and other factors on the academic staff membersâ€™ intentions to depart from or remain at the three universities. The study revealed that the effect of these factors on the academic staffâ€™s intention to depart or remain varied across the three universities . The study concluded that age, educational level, rank, employment status, marital status and area of specialisation were significant at HU but not at UKZN, where none of these factors were found to be significant predictors of a staff memberâ€™s intention to depart from the university. The findings of this study will enable higher education leaders and human resource practitioners in general, but Ethiopian institutions in particular, to design an acceptable human resource strategy and policy, tailored to address diversity and overcome the temptations of â€œone- size - fits - allâ€ retention strategies.